Core-doped Nd:YAG disk solar laser uniformly pumped by six Fresnel lenses - Garcia, Dário (2021)
A novel solar laser uniformly pumped by six Fresnel lenses is proposed here. The incident solar radiation is firstly collected and concentrated by six 0.8 m diameter Fresnel lenses and then reflected by other six plane mirrors to a central focal zone, where a laser head is mounted. About 2.5 kW solar power with 3.5 W/mm2 peak solar flux can be achieved in the focal zone. The laser head is composed of a fused silica six-sphere type secondary concentrator that further compresses the concentrated solar power from the six Fresnel lenses-plane mirrors to a core-doped YAG Nd3+:YAG ceramic disk. Optimum pumping parameters and solar laser output powers are found through ZEMAX non-sequential ray-tracing and LASCAD laser cavity analysis, respectively. The laser resonant cavity is formed by a PR 1064 nm output coupler and a HR 1064 nm plane reflector. An 8 mm diameter central hole is drilled through the six-sphere type concentrator to allow the extraction of laser power from the disk. Since only 16 % of the useful solar power is absorbed by the Nd:YAG medium, for 950 W/m2 of terrestrial solar irradiation, the effective solar pump power of 456 W is assumed in ray-tracing analysis. 72.2 W of multimode laser power is predicted for an 8 mm diameter gain medium embedded within a conical undoped YAG cladding, reaching the collection efficiency of 24.1 W/m2. M2 = 16.6 is numerically calculated, corresponding to the brightness figure of merit of 0.26 W. A near uniform absorbed pump profile is achieved.